2019
DOI: 10.1111/hepr.13460
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of objective response rate, progression‐free survival, and adverse events in hepatocellular carcinoma patients treated with lenvatinib: A multicenter retrospective study

Abstract: Aim The aim of this study was to investigate the predictive factors of objective response rate (ORR) and progression‐free survival (PFS), and the correlation of albumin‐bilirubin (ALBI) grade with decreased appetite and fatigue in hepatocellular carcinoma patients treated with lenvatinib. Methods From March 2018 to December 2018, a total of 94 patients was included in this retrospective multicenter study. Results The median age of all patients was 73 years (interquartile range 66–79.3 years), and approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
6
34
1
Order By: Relevance
“…In the present study, median PFS was 5.0 months, which was shorter than that in the phase 3 REFLECT trial, revealing median PFS was 7.4 months in the overall population and 7.2 months in the Japanese subset [18]. However, in real-world settings, median PFS ranging from 4.4 to 5.4 months has been reported, consistent with our results [19,20]. This may be explained by more patients in real-world settings being aged and having low ECOG-PS score and Child-Pugh score compared with the clinical trial.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, median PFS was 5.0 months, which was shorter than that in the phase 3 REFLECT trial, revealing median PFS was 7.4 months in the overall population and 7.2 months in the Japanese subset [18]. However, in real-world settings, median PFS ranging from 4.4 to 5.4 months has been reported, consistent with our results [19,20]. This may be explained by more patients in real-world settings being aged and having low ECOG-PS score and Child-Pugh score compared with the clinical trial.…”
Section: Discussionsupporting
confidence: 90%
“…This is probably because the patients with good liver function and PS were initially received full dose, as shown in Table 7 , resulting in well-preserved liver function and PS after lenvatinib treatment. While dose reduction or starting dose was not influence on the decreased efficacy of sorafenib therapy [ 30 ], relative dose intensity was associated with efficacy of lenvatinib treatment [ 31 , 32 ] and adverse events were manageable in patients with good liver function [ 11 , 12 ]. Therefore, the patients with good liver function were likely to receive initial full dose of lenvatinib, indicating that the initial full dose was found to be significant factor.…”
Section: Discussionmentioning
confidence: 99%
“…The REFLECT trial [ 8 ] revealed that lenvatinib showed non-inferiority to sorafenib in terms of overall survival (OS) and a statistically significant improvement in the objective response rate (ORR) and progression-free survival (PFS). Lenvatinib has recently become available as the first-line systemic therapy and showed the ORR of 30.4 to 39.0 % and the median PFS of 5.4 to 7.6 months in clinical settings [ 9 , 10 , 11 , 12 ]. Moreover, regorafenib [ 13 ] and cabozantinib [ 14 ] demonstrated efficacy in second-line treatment and ramucirumab [ 15 ] also provide the better outcome in patients with α-fetoprotein (AFP)≧ 400 ng/mL.…”
Section: Introductionmentioning
confidence: 99%
“…1,19 Other studies reported that AEs related to lenvatinib treatment more frequently occurred in patients with poor liver function (ALBI grade 2 or 3) at the time of lenvatinib initiation. 3,20 It has been verified that preserved liver function (ALBI grade 1) is important to the achievement of a favorable therapeutic response while high dosages were maintained. [3][4][5]21 However, not all patients with deteriorated liver function (ALBI grade 2 or 3) will be contraindicated to lenvatinib.…”
Section: Discussionmentioning
confidence: 99%
“…However, lenvatinib treatment is not generally recommended for all patients with ALBI grade 2 or 3, because AEs are more severe in such patients than in patients with ALBI grade 1. 3,20 Further studies are required to confirm the strategy of lenvatinib treatment for patients with advanced portal hypertension. For most anticancer drugs, the pharmacokinetic profile of drug exposure in patients with poor liver function has been discussed.…”
Section: Discussionmentioning
confidence: 99%